Upaya Peningkatan Minat Baca dan Pengetahuan Siswa Melalui Model Pembelajaran Inkuiri di MTs. Miftahul Huda Jleper Demak Jawa Tengah - Anisah, Noor (Jurnal Paedagogy, 2020)
This study aims to increase students' reading interest and knowledge by using an inquiry model. This research method uses Classroom Action Research. The study population used all class VIII students of MTs Miftahul Huda Jleper for the 2020/2021 academic year and the subjects of this study were students of class VIII-C. This data collection technique used tests and observations, while the data analysis techniques used quantitative and qualitative descriptive analysis. The results of this study indicate that the average observations of the syntax implementation of the inquiry learning model in each cycle are; the first cycle (74.5%), the second cycle (83.3%), the third cycle (92.7%). The results of the average value of learning assessments and the number of students who completed learning in each cycle, namely cycle I had an average value of 76 with students who completed 16, cycle II had an average value of 82 with students who completed 21, and cycle III had an average score of 82. average score 91 with students who completed 28 students. Based on the reading interest questionnaire, it was obtained an increase in each cycle, namely in cycle I (65.2%), cycle II (79.7%), and cycle III (87.6%).